If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 16 + -3x + -4y Solving 0 = 16 + -3x + -4y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 0 + 3x = 16 + -3x + 3x + -4y Remove the zero: 3x = 16 + -3x + 3x + -4y Combine like terms: -3x + 3x = 0 3x = 16 + 0 + -4y 3x = 16 + -4y Divide each side by '3'. x = 5.333333333 + -1.333333333y Simplifying x = 5.333333333 + -1.333333333y
| 13x+9=3x+9 | | -51=-2(1-5n)-(1-6m) | | x(6x-7)=o | | 5r^2-46r+48=0 | | 2q+3=11 | | 4a+2b+c=1000 | | 2x+8=2(1+2x) | | 5n^2+38n-63=0 | | -7c+4-c=-2(c+3) | | -2x(x+5)=3x-15 | | 0x+8=20 | | 4x-10=-4x | | N^2/2n-1 | | 3(3x+4)=3x+18 | | 10a=3.5(17) | | 2x+58=3(2+5x) | | 8x-(4x+7)+11=2x | | 7v^2-2v=0 | | 2a+6-6a= | | -(6m+4)=4m-2(6m+2) | | 9a+3b+c=1750 | | -4k+2(5k-6)= | | 20n^2-16n-160=0 | | -4/.75 | | 81x^2-1/16 | | 5+6y-18y= | | 3y+2y-8=17 | | 4x+8=2(3+x)+2(x+1) | | (6x-10)(4x-9)= | | 2x^2+10x-85=0 | | x-6=9-4x | | 2n^2+25n+63=0 |